ANALYSIS OF SOCIAL INTERACTION AS A SURVIVAL STRATEGY FOR TRADITIONAL TRADERS IN THE DIGITAL ERA - Nasution, Amalia; Khairiah, Dian; Ritonga, M Akmal Parlindungan; Maulida, Tasya (PERSPEKTIF: Journal of Social and Library Science, 2024)
This study aims to analyze the survival strategies implemented by traditional traders in the Monza Sambu tax in the social and cultural context in the digitalization era. The method used is qualitative with a descriptive approach, involving data collection techniques through in-depth interviews, observations involving several techniques such as direct observation, informal interviews, and documentation of physical conditions. This study found that traditional traders face significant challenges due to digital developments. In addition, traders also apply local cultural values ​​​​to maintain their identity amidst the flow of modernization. The results of this study found that traders in the Sambu tax face the challenge of transitioning to the digital market is not easy, although some traders realize the importance of the existence of online markets, but not all of them have the ability or facilities to sell digitally, this adds to the difficulty for them to continue to compete with the increasingly growing digital market, not only the transition to the digital market is a challenge for traders infrastructure and weather constraints are also challenges.